Self-Assembly of Tail Tube Protein of Bacteriophage vB_EcoS_NBD2 into Extremely Long Polytubes in E. coli and S. cerevisiae - Špakova, Aliona (Viruses, 2019)
Nucleotides, peptides and proteins serve as a scaffold material for self-assembling nanostructures. In this study, the production of siphovirus vB_EcoS_NBD2 (NBD2) recombinant tail tube protein gp39 reached approximately 33% and 27% of the total cell protein level in Escherichia coli and Saccharomyces cerevisiae expression systems, respectively. A simple purification protocol allowed us to produce a recombinant gp39 protein with 85%–90% purity. The yield of gp39 was 2.9 ± 0.36 mg/g of wet E. coli cells and 0.85 ± 0.33 mg/g for S. cerevisiae cells. The recombinant gp39 self-assembled into well-ordered tubular structures (polytubes) in vivo in the absence of other phage proteins. The diameter of these structures was the same as the diameter of the tail of phage NBD2 (~12 nm). The length of these structures varied from 0.1 µm to >3.95 µm, which is 23-fold the normal NBD2 tail length. Stability analysis demonstrated that the polytubes could withstand various chemical and physical conditions. These polytubes show the potential to be used as a nanomaterial in various fields of science.